(untitled) (Research, Society and Development, 2022)
Organizational management is a tool that must assess and recognize the evolution of company management in all sectors; thus, the various practices published in people management programs offer examples of innovation and creativity in carrying out production processes that deserve and need to be disseminated to be used as management models in other organizations. This article aims to identify and analyze the importance of temporary work for organizations, offering subsidies, characterizing the advantages and disadvantages, thus promoting a suggestion for the implementation of this Human Resources management system aimed at improving the provision of services and the realization of organizational objectives. This is an exploratory and descriptive study, supported by bibliographic research. A questionnaire was also applied in two public companies. The results showed that in the human resources practices of the organizations surveyed, practices aimed at planning, encouraging employees’ creativity and evaluating the organizational climate were identified. The study concludes that the outsourcing of labor in services is an alternative endorsed by the relevant legislation, which, between advantages and disadvantages, has its practice linked to cost reduction and greater flexibility in the operation of the services provided to the customer.